Diretrizes para o gerenciamento do saneamento ambiental com ênfase aos resíduos sólidos em aglomerados urbanos da bacia do Rio Gramame - Gurgel, Pablo Moreno Feitosa (2006)
The growth of cities and the appearance of occupations of disordered form are great problems to be faced by the Public Power. The maintenance of welfare conditions of the population doesn t develop in the same speed that the accumulations appear, that it makes impracticable adequately efficient solutions to the infrastructure demands and public services. The not-attendance of these demands allows that the population develops inadequate solutions, being able to generate great impacts to the environment and the welfare of everyone. In regards to the solid residues, the national scene is preoccupying. The majority of the Brazilian cities still destine its garbage of inadequate form, in garbage place. Although the cities not to possess budget adjusted to accomplishment of regular and efficient services of public cleanness, the population also doesn t contribute, developing inadequate habits in the handling of the solid residues. The study allows to verify the conditions that find the inserted urban accumulations in the basin of river Gramame. It can be perceived that in the majority of the studied accumulations the service of regular urban cleanness is developed. However, some inhabitants of that place don t adopt the collection, destining the garbage of inadequate form. In the accumulations that don t make use of the service, the adopted solutions are the burning, to embed the residue or simply to destine it on the ground. Although the communities possess associations, the actions of reduction and reuse of residues are spread out of discrete form. After evaluation of the partner-economic and ambient aspects of the studied accumulations, verified which of these is the most deficit if treating existing demands and was proposal an alternative of management of the solid residues, being able to be used in the others inserted accumulations in the basin or of other regions, with similar characteristics.